The Kibera Soweto East Project in Nairobi, Kenya - (:unkn) unknown (My University, 2011)
This article analyses the pilot public housing project in Kibera Soweto East in Nairobi under the Kenya Slum Upgrading Programme (KENSUP), courtesy of a partnership between the Government of Kenya and the United Nations Human Settlements Programme (UN-HABITAT), which began in 2004. The article examines the process of temporary relocation of Soweto East Zone A residents, seven years after the launch of this project, and takes a critical look at the effects of this relocation on the affected population. In order to achieve this, data on Soweto East will first be presented followed by information obtained from surveys conducted on Soweto East residents by Amnesty International and UN-HABITAT. The temporary relocation of residents shall then be analysed with reference to book reviews, interviews and site visits. Finally, the key points analysed within this article shall be presented briefly along with the recommendations derived from this study.
Keywords: African Research